Clinical and genomic characterization of carbapenem-resistant Enterobacterales bloodstream infections in patients with hematologic malignancies - Chen, Yi; Huang, Jiangqing; Dong, Luyan; Xu, Binbin; Li, Lei; Zhao, Zhichang; Li, Bin (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundCarbapenem-resistant Enterobacterales (CRE) bloodstream infections (BSIs) pose a significant risk to patients with hematologic malignancies, yet the distinct features and outcomes of these infections are not thoroughly understood.MethodsThis retrospective study examined the characteristics and clinical outcomes of patients with Enterobacterales BSIs at the Hematology Department of Fujian Medical University Union Hospital from 2018 to 2022. Whole-genome sequencing was conducted on 45 consecutive CRE BSI isolates during this period.ResultsA total of 301 patients with Enterobacterales BSIs were included, with 65 (21.6%) cases of CRE and 236 (78.4%) cases of carbapenem-susceptible Enterobacterales (CSE). CRE infections accounted for 16.9% to 26.9% of all Enterobacterales BSIs, and carbapenem-resistant Klebsiella pneumoniae (CRKP) was the predominant strain. The most frequent sequence type (ST) and carbapenemase among CRKP were ST11 (68.6%) and blaKPC-2 (80.0%), respectively. Perianal infections, multiple infection foci, and a history of multiple hospitalizations, ICU stays, and prior CRE infections were identified as risk factors for CRE BSIs. Patients in the CRE group experienced significantly higher proportions of infection-related septic shock (43.1% vs. 19.9%, P < 0.0003) and 30-day all-cause mortality (56.9% vs. 24.6%, P < 0.0001) compared to those in the CSE group. Patient’s age and disease subtypes, strain subtypes, and antimicrobial treatment regimens significantly influenced survival in patients with CRE BSIs.ConclusionsCRE BSIs are a frequent complication in patients with hematological malignancies undergoing treatment and are associated with poor survival rates. A comprehensive understanding of risk factors and ongoing surveillance of prevalent strains are essential for the effective management of these infections.